2023
DOI: 10.1021/acsaem.2c03636
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of MoC and Mo2C to Boost Hydrogen Generation from Ammonia Borane Hydrolysis

Abstract: Ammonia borane has been proposed as a competitor to boost H 2 evolution via the catalytic hydrolysis reaction at mild temperatures. A series of carbon nanotubes (CNTs)-supported Ni−Mo x C catalysts with different Mo x C crystalline phases are controllably synthesized using a facile two-step impregnation method followed by the thermal treatment. The catalyst structure and physicochemical properties are studied. The incorporation of Mo x C is effective for enhancing the catalytic activity of Ni/CNTs, and the β-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…239,244 While controlling temperature, pressure, or size is typically sufficient for achieving specific crystal-phase transitions or growth in pure metals, controlling the crystal phases of metal carbides and nitrides often requires adjustments in the proportions of different elements and the use of unconventional synthesis methods such as solvothermal processes. 250,251 Additionally, because of this, further research efforts are needed to fully uncover the impact of crystal phases on a chemical reaction, particularly when considering variations in the composition ratio. Currently, there is relatively limited 252,253 It has been confirmed that these materials exhibit positive catalytic performance in nitrogen reduction reactions, and further improvements in catalytic activity can be considered from the perspective of crystal phases.…”
Section: Metal Nitridesmentioning
confidence: 99%
See 1 more Smart Citation
“…239,244 While controlling temperature, pressure, or size is typically sufficient for achieving specific crystal-phase transitions or growth in pure metals, controlling the crystal phases of metal carbides and nitrides often requires adjustments in the proportions of different elements and the use of unconventional synthesis methods such as solvothermal processes. 250,251 Additionally, because of this, further research efforts are needed to fully uncover the impact of crystal phases on a chemical reaction, particularly when considering variations in the composition ratio. Currently, there is relatively limited 252,253 It has been confirmed that these materials exhibit positive catalytic performance in nitrogen reduction reactions, and further improvements in catalytic activity can be considered from the perspective of crystal phases.…”
Section: Metal Nitridesmentioning
confidence: 99%
“…Unlike pure metals, which are limited to the fcc, bcc, and hcp crystal phases, metal carbides and nitrides exhibit greater structural complexity and a wider range of crystal phases due to the diverse coordination of metal and nonmetal atoms as well as nonuniform molar ratios. , While controlling temperature, pressure, or size is typically sufficient for achieving specific crystal-phase transitions or growth in pure metals, controlling the crystal phases of metal carbides and nitrides often requires adjustments in the proportions of different elements and the use of unconventional synthesis methods such as solvothermal processes. , Additionally, because of this, further research efforts are needed to fully uncover the impact of crystal phases on a chemical reaction, particularly when considering variations in the composition ratio. Currently, there is relatively limited research on the crystal phases of metal carbonitrides, with most of them centered around molybdenum atoms.…”
Section: Metal Carbides Nitrides Borides and Hydroxidesmentioning
confidence: 99%
“…Thermolysis and alcoholysis often require high-temperature operation over catalysts and may generate organic byproducts. In contrast, hydrolysis is the simplest method, only requiring the assistance of a catalyst under ambient conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, nickel-based electrocatalysts have been reported to show good HER and OER performances in alkaline media. 20,21 However, their limited surface-active species impact mass transfer and overall electrocatalytic performance. 22,23 To resolve this issue, several researchers have attempted to improve the catalytic performances by doping the matrix with heteroatoms, 24,25 formulating hybrid heterostructures, 26 and growing electroactive matrices on conducting material substrates.…”
Section: Introductionmentioning
confidence: 99%